2016
DOI: 10.1021/acs.jproteome.6b00109
|View full text |Cite
|
Sign up to set email alerts
|

New Nordic Diet versus Average Danish Diet: A Randomized Controlled Trial Revealed Healthy Long-Term Effects of the New Nordic Diet by GC–MS Blood Plasma Metabolomics

Abstract: A previous study has shown effects of the New Nordic Diet (NND) to stimulate weight loss and lower systolic and diastolic blood pressure in obese Danish women and men in a randomized, controlled dietary intervention study. This work demonstrates long-term metabolic effects of the NND as compared with an Average Danish Diet (ADD) in blood plasma and reveals associations between metabolic changes and health beneficial effects of the NND including weight loss. A total of 145 individuals completed the intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 82 publications
1
48
0
Order By: Relevance
“…and fatty acid metabolism (PCs and plasmalogens). Interestingly, the GC–MS and LC–MS analytical platforms provided complementary information on the dietary items and mechanisms; GC–MS detect fewer metabolites, but the better analytical precision results in almost the same number of discriminating metabolites for the two diets. These represent fish, fruit/vegetables, and whole grain similar to LC–MS, although larger number of food intake markers were observed with LC‐MS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…and fatty acid metabolism (PCs and plasmalogens). Interestingly, the GC–MS and LC–MS analytical platforms provided complementary information on the dietary items and mechanisms; GC–MS detect fewer metabolites, but the better analytical precision results in almost the same number of discriminating metabolites for the two diets. These represent fish, fruit/vegetables, and whole grain similar to LC–MS, although larger number of food intake markers were observed with LC‐MS.…”
Section: Discussionmentioning
confidence: 99%
“…A better understanding of the relation between dietary patterns and metabolic profiles is crucial for improving nutritional advice, but the dietary factors contributing to the change often remain elusive . Several studies have already demonstrated that different dietary intake patterns are visible in metabolomics data . Some metabolites are also well known to reflect intakes of specific foods .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, ASCA was employed in order to investigate the importance of each factor in the dataset and to extract them from the global matrix. ASCA permutation test ( n = 2000) was performed to validate significance of all three main effects, country, gender, and economic status, and their two‐factor interaction terms, as described previously . Finally, PLS‐DA was carried out on the “economic status effect separated data matrix” from ASCA and validated according to Khakimov et al .…”
Section: Methodsmentioning
confidence: 99%
“…In the NND study, plasma metabolome analyses (measurement of all types of metabolites in plasma) that linked weight changes and improved insulin sensitivity to metabolic processes such as increased ketosis and increased gluconeogenesis were also undertaken (23).…”
Section: Glucose Metabolism and Insulin Sensitivitymentioning
confidence: 99%